CRITICAL DISCOURSE ANALYSIS OF SARA MILLS MODEL ON THE SHORT STORY “SI MONTOK” BY A.A NAVIS - Defianty, Rina; Karyani, Afril Lita; Putri, Farhanasyah; Handayani, Sri; Asmara, Trinata; Suryani, Suryani (LUMBUNG AKSARA, 2025)
This study analyzes the short story ‘Si Montok’ by A.A. Navis using Sara Mills’ critical discourse analysis model, focusing on the representation of women in the text and how the text reconstructs power relations in society. This analysis aims to reveal how the discourse in the short story presents and perhaps challenges the construction of gender and power in society. Through the analysis of the positions of the subject, object, and reader in the narrative structure, this study finds that the short story ‘Si Montok’ tends to represent women from a male perspective, objectifies women’s bodies, and reinforces existing social stereotypes of women. This analysis is expected to enrich Indonesian literary studies with a critical discourse analysis perspective, especially Sara Mills’ model, which emphasizes the importance of social and political context in understanding the text.